1974
DOI: 10.1113/jphysiol.1974.sp010705
|View full text |Cite
|
Sign up to set email alerts
|

Calcium movements in single crustacean muscle fibres

Abstract: 1. Internal microinjection of the Ca‐sensitive photoprotein aequorin or the isotope 45Ca have been used to assess Ca movements in single muscle fibres from the barnacle Balanus nubilus and the crab Maia squinado. 2. Progressive isosomotic replacement of external Na by Li, choline, sucrose or Tris was associated with a rapid increase in the level of light emission from internally injected aequorin. This response was dependent upon the presence of external Ca. The light output was maximal for Na concentrations <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…After incubation in Na-free (Tris) solution, the 45Ca efflux was measured (Table 2B), and the value was compared with that obtained in tissues with a low concentration of [Ca]j. The [Ca]j-activated 45Ca efflux (Baker & McNaughton, 1976;Blaustein, 1977), cardiac muscle (Reuter & Seitz, 1968;Busselen & Kerkhove, 1978), barnacle muscle (Ashley et al 1974;Russel & Blaustein, 1974) and brain synaptosome (Blaustein & Ector, 1976). Fig.…”
Section: -2 Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After incubation in Na-free (Tris) solution, the 45Ca efflux was measured (Table 2B), and the value was compared with that obtained in tissues with a low concentration of [Ca]j. The [Ca]j-activated 45Ca efflux (Baker & McNaughton, 1976;Blaustein, 1977), cardiac muscle (Reuter & Seitz, 1968;Busselen & Kerkhove, 1978), barnacle muscle (Ashley et al 1974;Russel & Blaustein, 1974) and brain synaptosome (Blaustein & Ector, 1976). Fig.…”
Section: -2 Resultsmentioning
confidence: 99%
“…In squid axon (Baker & McNaughton, 1976;Blaustein, 1977), cardiac muscle (Reuter & Seitz, 1968;Busselen & Kerkhove, 1978), barnacle muscle (Russell & Blaustein, 1974; Ashley, Ellory & Hainaut, 1974) and brain synaptosome (Blaustein & Ector, 1976), it has been proposed that necessary energy for uphill transport of the Ca ions is derived from the energy of the Na gradient across the plasma membrane. However, an active Ca-pump mechanism involved in the Ca extrusion in the above tissues cannot be ruled out (DiPolo, 1974;Baker & McNaughton, 1976;DiPolo & Beauge, 1979), and the role of ATP in the [Na]o-activated Ca efflux remains unknown (Baker & Glitsch, 1973;Jundt & Reuter, 1977;Blaustein, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the evidence favours the view that the fall of aya in low Nao was because of a Na efflux in exchange for either Ca or Mg, a system similar to that found in other crustacean muscles (Baker, 1972;Ashley & Ellory, 1972;Ashley, Ellory & Hainut, 1974). Firstly, changes of aj a were very sensitive to the size of the Na gradient across the membrane; secondly, the effect was inhibited by the elements Co, Mn and La in concentrations which have been found to inhibit Na/Ca exchange in squid giant axon (see Baker, 1972) and thirdly, there was always very little change in membrane potential during such large changes of ai a suggesting that the Na/Ca (or Mg) exchange might be electroneutral.…”
Section: Effect Of Changes In the External Phmentioning
confidence: 99%
“…It was found however after long exposure to either drug that large contractures occurred whenever Na0 was reduced for more than 2-3 min. Ashley & Ellory (1972) and Ashley, Ellory & Hainut (1974) have reported that D600 has no effect on the …”
Section: Effects Of D600 and Verapamitmentioning
confidence: 99%
“…In some experiments the trivalent ion La was included in the external solution. This agent is known to reduce membrane Ca transport in these fibres (Ashley, Ellory & Hainaut, 1974) and thus should prevent a significant depletion of the more slowly equilibrating compartments (see Mayer, Van Breemen & Casteels, 1972). The fibre responsiveness to injected caffeine after exposure to the experimental salines was then re-assessed.…”
Section: Introductionmentioning
confidence: 99%